Inovação na epilação a laser: Triple wave de alta potência com resfriamento integrado - (:unkn) unknown (Universidade Brasil, 2024)
Introduction: The search for methods of permanent hair removal has increased in recent decades, with the common use of high-power laser in clinical practice. Recent innovations have focused on the simultaneous emission of different wavelengths and application modes such as super hair removal (SHR) and hair removal (HR), with the possibility of cooling the tip for increased comfort and safety. Objective: This study aimed to compare the efficacy and safety of simultaneous application of three wavelengths in a combined protocol using SHR and HR methods for selective photothermolysis of hair follicles, compared to traditional SHR and HR methods. Methods: Forty-eight female patients aged 18 to 45 were included and divided into 3 groups: SHR Group: participants received triple wave laser application in a sweeping motion across the axillary area; HR Group: participants received 21 spot shots with triple wave laser distributed throughout the axillary region; SHR+HR Group: participants received SHR mode for the first 3 sessions and HR mode for the subsequent 3 sessions, following the procedures described in the previous groups. Interventions were performed bilaterally in the axillae with 30-day intervals, totaling 6 sessions with a 30-day follow-up after the last session. Evaluation methods included photographic assessment for hair count, skin temperature measurement, pain assessment using a visual analog scale, and patient satisfaction using the GAIS scale. Results: All three application methods resulted in a significant reduction in hair count, with no statistical difference between them. Patient satisfaction did not differ significantly between groups, as all groups reported satisfaction with the application methods. Pain perception differed across sessions, with SHR and SHR+HR methods showing lower pain levels throughout all sessions compared to the HR group. Adverse reactions evaluated included occurrences of edema and erythema, observed 30 minutes after each application, primarily in the HR and SHR+HR groups. Axillary temperature variations were less pronounced in the SHR group. Conclusion: The triple wave laser with cooled tip is effective and safe for hair reduction, regardless of the application mode.
Keywords: Fotoepilação; Laser de alta potência; Triple wave; Epilação; Engenharia Biomédica (Bioengenharia)